Overwhelmed by beauty and faith: review on artistic and religious travelers’ syndromes - Cisneros-Ceh, Damaris; Esquivel-Heredia, Darina; Medina-Vargas, Allan; Azcorra-Perez, Hugo; Chi-Mendez, Claudia Guadalupe; Marin-Cardenas, Alina D.; Mendez-Dominguez, Nina (Frontiers in Behavioral Neuroscience, 2024)
Travelling with the intention to encounter with art or for purification of the spirit, involves a retribution of intangible nature and therefore, can be expected to be a positive experience; nevertheless, among susceptible travelers there is also a possibility to experience pathological conditions. Although it is colloquially known that beauty lies in the eyes of the beholder, it is necessary to mention that the appreciation of beauty, immensity or mysticism contained in masterpieces is not perceived only in the eyes, but rather, from their perception by the sense organs and comprehended within a cultural framework and previous knowledge. The reaction triggers a series of somatosensory responses of a diverse nature, with a wide range of responses that together constitute a pathological phenomenon that can be defined as syndromic by eliciting signs and symptoms of physical, physiological, and psychotic nature. Stendhal and Jerusalem syndromes are both travelers´ syndromes that may occur before objectively aesthetic elements, saturated with meaning linked to cultural heritage of contemporary humanity. Stendhal syndrome evokes physical and psychoemotional symptoms from contemplation of art, but Jerusalem syndrome goes beyond perception, adding delusions of being a religious or prophetic protagonist pursuing individual or collective salvation.